Avaliação dos níveis de vibração e ruído em motosserra, com motor dois tempos - Depoi, Juliano dos Santos (2020)
The forest harvesting operation is undeniably hard work and with a high risk of accidents, in addition to causing serious health problems for workers. Despite technological advances, chainsaws when operated continuously because damage to the operator's body, due to their mass and the wood's resistance to cutting, acting as a stressor. In this sense, the present study aimed to evaluate and quantify the level of noise emitted and the magnitude of vibrations that reach the hands and arms of the chainsaw operator. The work was carried out in the municipality of Santa Maria, Rio Grande do Sul. The variables evaluated were the level of vibration and noise, from the chainsaw in operation. Two cutting sets consisting of a semi-square and square tooth chain were used in different forest species (Eucalyptus grandis, Eucalyptus dunnii and Acácia mearnsii De Wild). The assessment of vibration and noise was based on the criteria established by Regulatory Standard NR-15, NHO 10, ISO 2631-4, NHO 01, respectively. The results of the vibration levels were higher than the reference limits established by ISO 2631-4. It was observed for both cutting sets that the highest levels of vibration occurred on the “x” axis. After processing the data, the acceleration values resulting from the normalized exposure to hand and arm vibrations showed significant differences for the “y” and “z” axes. The basic density of the wood and the cutting sets used did not influence the noise levels generated to the operator, and all evaluations emitted noises higher than the level recommended by ISO 2631-4, NHO 10 and NR-15. Therefore, it can be inferred that the chainsaw operation is potentially capable of causing damage to the health of workers as a stressor.